2018
DOI: 10.1097/spv.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ketorolac After Outpatient Urogynecologic Surgery: A Randomized Control Trial

Abstract: Intravenous ketorolac administered after outpatient transvaginal surgery did not result in a reduction of pain scores or total morphine consumption. There was one Dindo grade II complication in the ketorolac group. Larger randomized control trials are needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…23 Intraoperative use of nonopiate medications, such as intravenous toradol and belladonna opium suppositories have been shown to help with postoperative pain control after ureteroscopy. 11,24 Notably in this study, no surgical factors were identified as risk factors for persistent opiate use, including stent duration or sheath use. After surgery, providing a standardized MED per postoperative opiate prescription may help minimize the quantity of opiates prescribed and/or unused by patients.…”
Section: Discussionmentioning
confidence: 75%
“…23 Intraoperative use of nonopiate medications, such as intravenous toradol and belladonna opium suppositories have been shown to help with postoperative pain control after ureteroscopy. 11,24 Notably in this study, no surgical factors were identified as risk factors for persistent opiate use, including stent duration or sheath use. After surgery, providing a standardized MED per postoperative opiate prescription may help minimize the quantity of opiates prescribed and/or unused by patients.…”
Section: Discussionmentioning
confidence: 75%